Analysis of Factors Influencing Interest and Behavior in Using ShopeePay Features Using the Unified Theory of Acceptance and Use of Technology (UTAUT2) Model - Desvira, Nanda Suci; Aransyah, Muhammad Fikry (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
This research is motivated by technological developments that continue to provide innovations aimed at facilitating human work, such as innovations in payment methods that can be done digitally and non-cash, called digital wallets. One digital wallet with the most users in Indonesia is ShopeePay. However, the existence of ShopeePay has yet to be entirely accepted by digital wallet users in Indonesia, as shown through a consumer survey in 2022 which resulted in conclusions regarding ShopeePay experiencing a decline in users. This study intends to determine the factors that influence behavioral intention and use behavior of the ShopeePay feature as measured by the variables in the UTAUT 2 model. This quantitative study uses a survey method with 100 respondents using the ShopeePay digital wallet. Samples were taken using a purposive sampling technique. The data analysis technique used is the SEM-PLS method, and the data is processed using SMART PLS 4.0 software. The results of this study indicate that the factors that significantly influence the behavioral intention of the ShopeePay feature are social influence, price value, and habit. Then, the use behavior of the ShopeePay feature is significantly influenced by facilitating conditions and habits. Meanwhile, the performance expectancy, effort expectancy, facilitating conditions, and hedonic motivation variables do not have a significant effect on the behavioral intention of the ShopeePay feature.